Antimicrobial activity against periodontopathic bacteria and cytotoxic study of cratoxylum formosum and clausena lansium - Jintakorn Kuvatanasuchati (2018)
Cratoxylum formosum ssp. pruniflorum and Clausena lansium are among edible plants that commonly used for various ethnomedical conditions. This study investigated antimicrobial activity against periodontopathic bacteria using agar diffusion technique. These plant extracts demonstrated comparable antimicrobial efficacy against black-pigmented bacteria strains to standard drug chlorhexidine. The CD50 of C. formosum and C. lansium on HGF cells were 0.37 and 0.16 mg/ml, respectively, demonstrated using the MTT assay. ©2011 Academic Journals.